ANALISIS ALIH FUNGSI LAHAN SAWAH MENJADI LAHAN TERBANGUN DI KOTA BUKITTINGGI - Ronaldo Sonet; Dwi Marsiska Driptufany; Defwaldi Defwaldi; Ilham Armi (Cross-border, 2023)
The City of Bukittinggi has developed into a center for tourism development in West Sumatra because of its natural and cultural characteristics, as well as its strategic location which has made it possible for the City of Bukittinggi. Land is the physical environment consisting of climate, relief, soil, water and vegetation as well as objects on it as long as there is an influence on land use, including the results of past and present human activities. The conversion of agricultural land to non-agricultural land use can theoretically be explained in the context of land economics which places land resources as a factor of production, where the point view that land is treated as a strategic commodity. The remote sensing data used is Landsat 8 OLI imagery for 2013, 2017 and 2022. Furthermore, classifying satellite imagery using the Supervised Classification method. Based on the results of processing satellite imagery in 2013, the area of paddy fields is 594.5 ha or 25.25% of the area of Bukittinggi City. The area of paddy fields in 2017 was 502.4 ha or 21.34% of the area of Bukittinggi City. Meanwhile, the area of paddy fields in 2022 is 427 ha or 18.14% of the area of Bukittinggi City. Based on the results of the change against paddy fields to built-up land in 2013-2017 paddy fields have decreased to become built-up areas of 118.3 ha. From 2017 to 2022 paddy fields have decreased to become built-up areas of 96.7 ha. And from 2013 to 2022 paddy fields have decreased to become built-up areas of 181.7 ha.